The Marian Anthem in Late Medieval England - Skinner, David E. (Studies in church history, 2004)
Alma redemptoris mater is one of the four ancient antiphons or anthems in honour of the Blessed Virgin Mary. This anthem may recall Chaucer’s Prioress’s Tale, and the image of a choirboy, seven years of age, who, having learnt his Alma redemptoris, sang daily the Virgin’s praises even beyond death. Primer in hand he learnt his Alma by heart, only to be murdered in a Jewish ghetto for singing the anthem that he took such pains to perfect. With the song on his lips his throat was cut; but Mary intervened, placed a precious pearl on his tongue, saying, My litel child, nowe wol I fecche thee,Whan that the greyn is fro thy tonge ytake.Be not agast; I wol the nat forsake.